Strategi pembangunan pariwisata internasional berbasis pertanian organik “shining batu” - Yusuf Adam Hilman (ARISTO, 2017)
Natural potential and also local knowledge possessed by Batu, a great asset that can be implied to improve the welfare of the community, through the program "Shining Batu". This study aims to look at how the tourism development strategy undertaken by the City of Batu. This study used qualitative methods, with some data collection techniques, such as: interviews, documentation, Batu via Program "Shining Batu" want to change Batu become central areas of organic farming, based tourism International, therefore, the development program of the region, the perceived has a lot of benefits to the people of Batu. At the core strategies that do include several steps, namely: mapping the existing potential, then design and validate the rule of law as the foundation for the implementation of the program, which is the umbrella law, after which it then processes Sounding program through the activities - the activities and the media.